International Market Integration for Natural Gas? A Cointegration Analysis of Gas Prices in Europe, North America and Japan - Anne Neumann; Boriss Siliverstovs; Guillaume L'Hégaret; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
We examine the degree of natural gas market integration in Europe, North America and Japan, between the mid 1990's and 2002. The relationship between the international gas marker prices, and their relation to the oil price, are investigated through principal component analysis and Johansen likelihood-based procedures. Both of them show a high level of integration within the European/Japanese and North American markets; but they also show that the European resp. Japanese and the North American markets were not integrated.
Keywords: L95; D43; C32; Q41; 330; Market Integration; gas markets; cointegration test; globalization; Erdgasmarkt; Erdgas; Preis; Marktintegration; Kointegration; Schätzung; EU-Staaten; Japan; Nordamerika